Consumer perceptions towards sustainable supply chain practices in the hospitality industry - Modica, Patrizia Daniela; Altinay, Levent; Farmaki, Anna; Gursoy, Dogan; Zenga, Mariangela (My University, 2020)
This study investigates the impacts of economic, social and environmental sustainability practices of companies in the hospitality supply chain on consumers’ satisfaction, loyalty and willingness to pay higher prices. Utilizing data collected from 288 tourists visiting south Sardinia, the study indicates that while economic sustainability practices have positive impacts on consumers’ satisfaction, loyalty and willingness to pay a premium, sustainability practices related to environmental and social dimensions have a direct positive impact on satisfaction and an indirect positive impact on consumer loyalty and willingness to pay a premium. Additionally, findings reveal that satisfaction is likely to mediate the impact of environmental and social sustainability practices on the loyalty of consumers. The theoretical and managerial implications of the study are provided.
Keywords: Consumer perceptions; Hospitality; Sardinia; Supply chain practices; Sustainability